Chapter Tra solidarietà europea e responsabilità nazionali: la tutela dei beni pubblici europei - Fontana, Olimpia (Studi e saggi, 2022)
The theme of solidarity between European Union (EU) member states lies at the heart of the European integration process itself, in the context of an ongoing tension between the renunciation of national sovereignty, driven by a drive for cooperation, and the maintenance of prerogatives of strategic interest to states. In fact, the EU was born from the decision of its members to pool selected aspects of their sovereignty, in a process whose evolution is expressed both in the choice of community policies and in the availability and methods of financing those policies. These are two sides of the same coin, that of the Community budget, which is the operational instrument that supports and accompanies the major steps in the EU's evolutionary process. Indeed, since the 1980s, the Community budget has represented the instrument capable of holding together on the one hand the process of economic liberalisation and on the other the objective of social integration between countries that had different starting conditions. However, cooperation and solidarity are aspects that need to be strengthened today, albeit in new dimensions. The financial crisis has brought about a new acceleration in the coordination of national fiscal policies, without, however, generating the missing piece to European economic policy, namely an autonomous fiscal capacity, endowed with taxation power, on which a full fiscal union would be based.